An Evaluation Method for Effective Prestress of Simply Supported Prestressed Concrete Beams with Breathing Cracks. (7th January 2021) - Guo, Wenlong; Liang, Peng; Liu, Hexu; Chen, Y. Frank; Zhao, Xiaojin
Abstract : Loss of effective prestress and accurate detection of actual stress in existing precast prestressed concrete bridges are two major challenges in the bridge industry. In this respect, this research aims at an improved method for the critical decompression moment (DM) test of cracked sections depending on the stress change rate of tensile rebars. A calculation method for total effective prestress of prestressing strands in the tensile region is derived with the assumption of the plane section and pre-decompression elastomer. The proposed method is verified by laboratory tests on beams and numerical analysis and by addressing effective prestress issues of existing simply supported beams. The determination results of the critical decompression state show that the proposed method (i.e., the stress change rate of tensile rebars-load curve) is more sensitive and reasonable than the traditional stress increment, i.e., load curve method. The evaluation results of the total effective prestress are more reasonable than the traditional method based on the steel stress relief hole technique or frequency test results. Compared with the existing methods for estimating the prestress using the mid-span deflection or crack width, the proposed method is more reasonable in theory and calculation. It provides a guide for the evaluation and reinforcement of aging bridges.